Establishment of an anaplastic stratification signature for gastric cancer based on diverse regulated cell-death - Chen, Shaofei; Wang, Zhiyong (Frontiers in Immunology, 2025)
BackgroundGastric cancer is a common malignant tumor characterized by poor prognosis and limited therapeutic options. The combination of Regulated cell death inducers and enhancement of the immune therapeutic effect plays an important role in cancer treatment.MethodsWe downloaded and analyzed data from gastric cancer samples, collected 14 Regulated cell death-related genes and constructed a Regulated Cell Death-Related Index (RCDRI) by various machine learning methods. Based on the RCDRI, gastric cancer patients were divided into high RCDRI and low RCDRI groups, and the clinical characteristics, immune cell infiltration, chemotherapy response and immunotherapy response of gastric cancer patients were analyzed based on the RCDRI.ResultsThe newly constructed RCDRI consisted of four Regulated cell death-related genes (CD36, SERPINE1, TRIML2, and GRP) and has been shown to be an effective predictive marker for the survival of gastric cancer patients and was trained with multiple external datasets. The high RCDRI group had a higher level of immune cell infiltration and better response to immunotherapy than the low RCDRI group. In addition, through pan-cancer analysis, we found that RCDRI can also be used for prognosis and immunotherapy prediction in a variety of cancers. Finally, in vitro experiments revealed that TRIML2 knockdown inhibited the proliferation and migration of gastric cancer cells.ConclusionsThe RCDRI identified in this study can accurately assess the prognosis and immunotherapy efficacy of gastric cancer patients, which lays a valuable foundation for future clinical treatment of gastric cancer.